Development of a Self-Coordinated Communication System for Scaring Birds on Rice Farms - Badru, Rahmon Ariyo (2015)
The study appraised techniques for communicating hazards to birds and developed a self-coordinated electronic communication system for scaring birds. It also determined the optimal placement of the bird-sensory electronic devices on the rice farms. This was with a view to solving the problem of menace of birds on rice farms.